Державні облігації як інвестиційний інструмент для населення в умовах цифровізації та воєнного стану - Пернарівський, Олександр Васильович (Сталий розвиток економіки, 2024)
У статті досліджено сутність та особливості державних цінних паперів як джерела покриття дефіциту державного бюджету та інвестиційного інструменту для населення в умовах цифровізації та воєнного стану. Охарактеризовано основні переваги облігацій внутрішньої державної позики, які зумовлюють їх популярність серед інвесторів. Проведено аналіз динаміки вкладень населення в облігації внутрішньої державної позики в умовах воєнного і виявлено її основні особливості. У ході аналізу охарактеризовано чинники, що впливають на фінансову поведінку в умовах воєнного стану. Визначено основні чинники інвестиційної привабливості облігацій внутрішньої державної позики для населення в умовах цифровізації та воєнного стану. Обгрунтовано необхідність застосування ефективної відсоткової ставки при визначенні інвестиційної привабливості облігацій внутрішньої державної позики для населення. Досліджено ризики населення при вкладанні коштів в державні цінні папери.

The article substantiates the relevance of the problem of analyzing the investment attractiveness of domestic government bonds in the conditions of digitization and martial state. The essence and purpose of domestic government bonds have been studied. It was established that domestic government bonds should be considered as a source of deficit coverage and an investment tool. Factors of investment attractiveness of domestic government bonds are analyzed. It was determined that one of the main factors of the investment attractiveness of domestic government bonds for the population is their profitability. The need to determine the effective interest rate when analyzing the profitability of investments is substantiated. A description of the main factors affecting the effective interest rate on investments in domestic government bonds is given. Formulas for determining the effective interest rate on investments in domestic government bonds and bank deposits are proposed. The dynamics of the population's investments in domestic government bonds during martial state is analyzed. The main factors influencing the financial behavior of citizens in the conditions of martial state are substantiated. The conducted analysis indicates that one of the features of the financial behavior of the population in the conditions of digitization and martial state is an increase in investments in domestic government bonds. The amount of such investments more than doubled during the period of martial state. This behavior of the population can be explained both by patriotic sentiments, which were especially evident in the middle of 2022, when investments in domestic government bonds, denominated in the national currency grew most rapidly, and by the growing investment attractiveness of these bonds. It has been established that, as of today, the effective rates for investments in domestic government bonds are higher than the effective rates for bank deposits. This difference is especially noticeable for long-term investments in the national currency. The main types of household risks when investing funds in domestic government bonds have been studied. It has been established that the level of risks of individuals for investments in domestic government bonds is almost the same as the level of risks for bank deposits.
Keywords: відсоткові ставки; державні цінні папери; ефективна ставка відсотка; інвестиційна привабливість ОВДП; ризики; interest rates; domestic government bonds; effective interest rate; investment attractiveness of DGB; risks